GENERATION Z INTEREST OF ENTREPRENEURSHIP IN PADANGSIDIMPUAN CITY (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2023)
The purpose of this study was to measure the influence of self-actualization, family environment, social media, and the pandemic situation partially and simultaneously on the interest of Generation Z in entrepreneurship in the city of Padangsidimpuan. The research method used is quantitative research with a population of 555 people and a sample of 233 people obtained using the Taro Yamane formula.The results of this study are partially self-actualization variables have a positive and significant effect on the interest of Generation Z in entrepreneurship in Padangsidimpuan City with tcount 7.777 > ttable of 1.971 and a significant value of 0.000 <0.05. The family environment variable has a positive and significant effect on the interest of generation Z in entrepreneurship in Padangsidimpuan City with a tcount 2.077 > ttable of 1.971 and a significant value of 0.039 <0.05. Social media variables do not have a positive and significant effect on the interest of Generation Z in entrepreneurship in Padangsidimpuan City with a tcount -0.365 < ttable of 1.971 and a significant value of 0.716 > 0.05. The pandemic situation variable also has no significant effect on the interest of Generation Z in entrepreneurship in Padangsidimpuan City with a tcount 1.040 < ttable of 1.971 and a significant value of 0.299 > 0.05. Simultaneously, the variables of self-actualization, family environment, social media, and the pandemic situation affect the interest of Generation Z in entrepreneurship in Padangsidimpuan City, which can be seen from the results of fcount 44,436 > f table of 2.253 and a significance value of 0.000 < 0.05 significance level.